2006
DOI: 10.1007/s10067-006-0501-1
|View full text |Cite
|
Sign up to set email alerts
|

A patient with hyper-IgD syndrome responding to anti-TNF treatment

Abstract: The hyperimmunoglobulinemia D periodic fever syndrome (HIDS) is caused by recessive mutations in the mevalonate kinase gene, which encodes an enzyme involved in cholesterol and nonsterol isoprenoid biosynthesis. The pathogenesis and treatment remains unclear. We describe a 6-year-old Turkish girl with severe disease. Her clinical features were accompanied with very high acute-phase reactants including a very high serum amyloid A level. The patient responded well to anti-tumor necrosis factor treatment. Our fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 7 publications
0
24
0
2
Order By: Relevance
“…Due to our knowledge, FMF and HIDS coexistence has not been reported before. HIDS registry in Nijmegen, Netherlands, currently has data on over 200 cases 126 of them were confirmed with mutation analysis and one of them from Turkey [10]. Our patient is the second Turkish case reported from Turkey, whose diagnosis was confirmed with homozygous V377I mutation analysis.…”
Section: Discussionmentioning
confidence: 52%
“…Due to our knowledge, FMF and HIDS coexistence has not been reported before. HIDS registry in Nijmegen, Netherlands, currently has data on over 200 cases 126 of them were confirmed with mutation analysis and one of them from Turkey [10]. Our patient is the second Turkish case reported from Turkey, whose diagnosis was confirmed with homozygous V377I mutation analysis.…”
Section: Discussionmentioning
confidence: 52%
“…[1,11,[14][15][16] Colchicine and prednisolone had no beneficial effect in preventing the recurrence of attacks in our patient. Recent studies with the HMG-CoA-reductase inhibitor simvastatin have brought hopeful results for the treatment of this disease [3,4,17,18] Simon et al [4] reported that six patients with HIDS and proven MVK deficiency were followed up for two treatment periods with simvastatin, 80 mg/day, or placebo for 24 weeks separated by a four-week washout period in a double-blind manner Important reductions in the number of attacks and decreased urinary mevalonate were observed.…”
Section: Discussionmentioning
confidence: 95%
“…Under these circumstances, the use of biological drugs (etanercept, IL-1 inhibitors) has allowed to manage febrile attacks recurrence according to certain anecdotal reports. 14,21,24,27 Other treatments, such as thalidomide, colchicine and simvastatin, were not effective. 28,29 …”
Section: Hereditary Periodic Fever Syndromes Familial Mediterranean Fmentioning
confidence: 99%